Spatial and vertical metals distribution in sediment cores from Kongkong Laut estuary, Masai, Johor - Khalid, Sara Azuana Khalidah; Mohamat Yusuff, Ferdius @ Ferdaus; Mohd Kusin, Faradiella; Arshad, Aziz; Ash'aari, Zulfa Hanan (Universiti Putra Malaysia Press, 2019)
Sediment has been widely used as a means for assessing the impact of anthropogenic activities on aquatic environment, with metal pollution being the most well-known threat to aquatic environments. Therefore the aim of this study is to identify and determine metal concentrations, specifically that of copper (Cu), chromium (Cr), cadmium (Cd), iron (Fe), and zinc (Zn) on four sediment cores samples of KongKong Laut Masai Johor. The aqua regia method had been used to analyze Cu, Cr, Cd, Fe and Zn concentrations in sediment samples. Metal concentrations had then been determined through the use of flame atomic absorption spectrometry. The degree of metal contamination in sediment core samples had been determined through using Enrichment Factors (EF) and Geoaccumulation Indices (Igeo). From this study, the mean and standard deviation of metal concentrations in each sediment core sample were shown to be lower than the average shale concentration and lower than both the effects-range low (ERL) and effects-range median (ERM) parameters for aquatic toxicity. This information could be useful, serving as a baseline for evaluating the potential impacts of future development in the area.